A Case Study of Industrial Symbiosis to Reduce GHG Emissions: Performance Analysis and LCA of Asphalt Concretes Made With RAP Aggregates and Steel Slags - Bonoli, Alessandra; Degli Esposti, Anna; Magrini, Chiara (Frontiers in Materials, 2020)
The concept of sustainability in the road construction sector is a complex issue because of the various steps that contribute to the production and release of greenhouse gas (GHG) emissions. Addressing this issue, the European Commission has put various policy initiatives in place to encourage the construction industry to adopt circular economy (CE) and industrial symbiosis (IS) principles e.g., the use of recycled materials. Cooperativa Trasporti Imola (CTI), a company located in the Emilia-Romagna region (Italy), has been chosen for the current case study to examine practices, management and industrial symbiosis network among various companies in the road construction and rehabilitation sector. In this regard, the use of steel slags, obtained by the Electric Arc Furnace (EAF), and Reclaimed Asphalt Pavement (RAP), obtained by deconstruction and milling of old asphalt pavement has been investigated. Two mixtures of recycled hot Mix Asphalt (HMA) i) first were prepared incorporating different recycled material percentages for the wearing and binder course, respectively ii) then were characterized in terms of size distribution, strength modulus and volumetric properties, iii) and finally were compared to the performances of two mixtures entirely designed by virgin materials for the wearing and binder course, respectively. Therefore, the Life Cycle Assessment (LCA) tool was chosen to evaluate the environmental impacts that affect the designed road life cycle. The results show that recycling RAP and EAF slags in CTI batch plant provides benefits by reducing the consumption of virgin bitumen and aggregates and by reducing CO2eq emissions. Finally, practical implications on the use of recycled materials in new asphalt mixtures from a life cycle and industrial symbiosis perspective are provided.